2006
DOI: 10.1038/nature05047
|View full text |Cite
|
Sign up to set email alerts
|

A juvenile early hominin skeleton from Dikika, Ethiopia

Abstract: Understanding changes in ontogenetic development is central to the study of human evolution. With the exception of Neanderthals, the growth patterns of fossil hominins have not been studied comprehensively because the fossil record currently lacks specimens that document both cranial and postcranial development at young ontogenetic stages. Here we describe a well-preserved 3.3-million-year-old juvenile partial skeleton of Australopithecus afarensis discovered in the Dikika research area of Ethiopia. The skull … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
220
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(232 citation statements)
references
References 27 publications
8
220
0
4
Order By: Relevance
“…Nonetheless, two broad grades of locomotor anatomy can be distinguished within the last 4 million years of hominin evolution (Klein, 1999;Bramble and Lieberman, 2004;Conroy, 2005). Members of the older group, the australopithecines, were habitual terrestrial bipeds that retained several primitive features related to arboreal locomotion, including relatively long arms and short hind limbs, long, curved phalanges, and a funnel-shaped torso with narrow shoulders and superiorly oriented glenoid fossa (Aiello and Dean, 1990;Ward, 2002;Bramble and Lieberman, 2004;Alemseged et al, 2006). In contrast, members of the genus Homo possess a suite of derived post-cranial traits associated with greater cursoriality, including longer hind limbs, shorter pedal phalanges, and a rigid longitudinal plantar arch (Shipman and Walker, 1989;Aiello and Dean, 1990;Bramble and Lieberman, 2004).…”
Section: Q2mentioning
confidence: 99%
“…Nonetheless, two broad grades of locomotor anatomy can be distinguished within the last 4 million years of hominin evolution (Klein, 1999;Bramble and Lieberman, 2004;Conroy, 2005). Members of the older group, the australopithecines, were habitual terrestrial bipeds that retained several primitive features related to arboreal locomotion, including relatively long arms and short hind limbs, long, curved phalanges, and a funnel-shaped torso with narrow shoulders and superiorly oriented glenoid fossa (Aiello and Dean, 1990;Ward, 2002;Bramble and Lieberman, 2004;Alemseged et al, 2006). In contrast, members of the genus Homo possess a suite of derived post-cranial traits associated with greater cursoriality, including longer hind limbs, shorter pedal phalanges, and a rigid longitudinal plantar arch (Shipman and Walker, 1989;Aiello and Dean, 1990;Bramble and Lieberman, 2004).…”
Section: Q2mentioning
confidence: 99%
“…The dilemma posed by the kipunji juvenile is analogous to that encountered by paleontologists, who must infer the adult morphology of juvenile fossils to determine their taxonomic affinities (e.g., Tobias, 1978;Alemseged et al, 2006;McNulty et al, 2006). In such cases, developmental simulation of adult cranial shape has proved useful for exploring ontogenetic differences among species and for testing taxonomic hypotheses Richtsmeier and Walker, 1993;Ackermann and Krovitz, 2002;McNulty et al, 2006).…”
Section: Developmental Simulationmentioning
confidence: 99%
“…The connection between the ventricles and the air sac passes underneath this bulla. Hyoid bones sometimes fossilize, and it has been DOI: 10.2478/v10235-011-0002-5 found that Neanderthals (Arensburg et al 1989, Arensburg et al 1990 and Homo heidelbergenis (Martínez et al 2008) have a hyoid bone without a bulla, while Australopithecus afarensis (Alemseged et al 2006) appears to have a bulla. This indicates that air sacs disappeared somewhere between 3.3 million years ago and 500 000 years ago in human evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The hyoid bone (Figure 1) is the only bony part of the vocal tract and the muscles of the larynx and the tongue connect to it. The hyoid bone has a cup shaped extension (called the hyoid bulla) in gorillas, chimpanzees and bonobos, but lacks this cup shaped extension in humans (Kohlbrugge 1896, Brown & Ward 1988, Aiello & Dean 2002, Alemseged et al 2006, Fitch 2009). The connection between the ventricles and the air sac passes underneath this bulla.…”
Section: Introductionmentioning
confidence: 99%